Landlord and tenant in a colonial economy: The Transvaal, 1880-1910 - Trapido, Stanley (My University, 1977)
A secret society with the professed aim of the 'promotion of all the interests of the Afrikaner nation'. (3) the Afrikaner Broederbond (hereafter the A.B. or Bond) has long been the bogeyman of South African politics. Its operations are attacked as detailed and lurid conspiracies, and defended as the innocent, confidential actions of public-spirited men. In the process, though much authoritative data on the Bond exists, its nature, functions and role have been thoroughly mystified. At the outset it must be stated that the A.B. has exerted a profound influence at all levels of South African politics. This paper attempts the beginnings of a demystification of the Bond's operations and an assessment'of its role up till 1946. Given its secret nature, this is necessarily sketchy and schematic. Yet such an assessment requires more than ideological forms with those of the new capitalism.
African Studies Seminar series. Paper presented December 1977. Not to be quoted without the Author's permission.
Keywords: Land tenure. South Africa; Landlord and tenant. South Africa. Transvaal. History